Non-thermal plasma coupled with CM/Z5 catalyst for toluene removal. Issue 1 (31st December 2022) - Liu, Jinbao; Zhang, Fen; Sun, Xianzhi; Tan, Tiantian; Liu, Qian; Liu, Xiaojie; Li, Bo
ABSTRACT: Based on the important effect of catalysts on the plasma-catalytic system, the CM/Z5 catalyst prepared by the incipient-wetness impregnation method is used for non-thermal plasma catalysis for toluene removal. The low-temperature plasma used is produced by dielectric barrier discharge. Toluene removal performance with single plasma is investigated by variation in experimental parameters. Results indicate that with the increase in discharge length, the selectivity of carbon dioxide increased.  With the increase in toluene concentration and gas flow rate, carbon dioxide selectivity decreases gradually, while toluene conversion shows almost no difference. With the introduction of CM/Z5 catalyst into the back end of plasma, the toluene conversion rate and carbon dioxide selectivity could be significantly improved and ozone in the exhaust gas could be eliminated to meet emission standards at the same time. This work is meaningful in promoting the industrial application of plasma catalytic coupling technology to treat volatile organic compounds.